2011
DOI: 10.1007/s10265-011-0463-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pollen supply and quality on seed formation and maturation in Pinus densiflora

Abstract: To understand the detailed mechanisms underlying variations in seed productivity per cone, it is important to examine simultaneously the effects of two pollination mode components (pollen supply and quality) on two seed production processes (seed formation and maturation). We conducted artificial pollination experiments with four pollination treatments (selfing, polycross, no-pollination and open-pollination treatments) in each of two vertical crown layers (upper and lower) for 19 Pinus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…We did not find a reduction in the proportion of full seeds with elevation, which would be the first negative outcome of selfing in other Pinus species (Iwasaki et al, 2013). Contrarily, our results suggest that seed development on the Pinus uncinata alpine treeline could be more influenced by low pollen supply at higher elevations (Iwaizumi & Takahashi, 2012). The decrease in the production of full seeds found along the gradient in our study sites is not accompanied by a reduction in the number of cones produced per tree (see Appendix ), nor in the weight of the seeds or in their viability.…”
Section: Discussionmentioning
confidence: 70%
“…We did not find a reduction in the proportion of full seeds with elevation, which would be the first negative outcome of selfing in other Pinus species (Iwasaki et al, 2013). Contrarily, our results suggest that seed development on the Pinus uncinata alpine treeline could be more influenced by low pollen supply at higher elevations (Iwaizumi & Takahashi, 2012). The decrease in the production of full seeds found along the gradient in our study sites is not accompanied by a reduction in the number of cones produced per tree (see Appendix ), nor in the weight of the seeds or in their viability.…”
Section: Discussionmentioning
confidence: 70%
“…Pollen quantity and quality provide in measuring and forecasting several factors, e.g. crop yield in trees (Allison, 1990;Hirayama et al, 2005;Iwaizumi & Takahashi, 2012) and yield in agriculture crops (Westgate et al, 2003), fruit size and production of seeds (Faegri & Iversen, 1989;McKone, 1990;Baskin & Baskin, 2018), ancient and current vegetation (Moore et al, 1991;Rogers, 1993;Obigba, 2021) and respiratory allergy symptoms from specific taxa to human beings (Filon et al, 2000;Gioulekas et al, 2004;Damialis et al, 2011;Sousa-Silva et al, 2021). In the present study the amount of pollen produced by individuals of selected five species was considered as pollen quantity which can be consumed by the animals and can be lost to the environment (through abiotic factors).…”
Section: Discussionmentioning
confidence: 99%
“…In a physiology study for P. densiflora , a 50% reduction in photosynthetic photon flux density (PPFD) caused a 10% to 15% reduction in net photosynthetic rate ( V cmax ; calculated from regression coefficients by Han, Kawasaki, Katahata, & Chiba, 2003). As costs for cone construction are much greater than those for seed production within the cone (Iwaizumi et al, 2008; Iwaizumi & Takahashi, 2012), the larger investment per cone in populations likely to have lower resource availability would achieve higher seed productivity per cone development cost in terms of resource‐use efficiency (Iwaizumi et al, 2019). The larger cones and higher seed productivity per cone found in trees of populations on the Japan Sea side could be due to adaptive or plastic responses that increase reproductive success by maximizing the number of seeds in a smaller number of cones.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have suggested that cone variation, such as cone size or thickness of scales in Pinus , should have adaptive significance as a means to maintain seed production and may be the responses to protect against snowfall or low temperature (Farjon & Styles, 1997; Gil et al, 2002; Linhart, 1978). As cone development carries a high cost to achieve seed production (Despland & Houle, 1997; Goubitz, Werger, Shmida, & Ne'eman, 2002; Iwaizumi & Takahashi, 2012), producing relatively highly reproductive cones is important for maximizing reproductive success in consideration of the development cost, particularly in environments with low temperature, less solar irradiance or less sunshine (Iwaizumi, Ohtani, & Takahashi, 2019). If environmental factors impact cone morphology, geographical variation linked to key influential climate differences is expected among populations or regions.…”
Section: Introductionmentioning
confidence: 99%